INTERVENTIONAL STUDY OF IMMEDIATE AND LONG TERM CHANGES IN HIV/AIDS KNOWLEDGE AND ATTITUDE AMONG SCHOOL STUDENTS IN AN URBAN SLUM IN MUMBAI - Padhyegurjar, Manasi Shekhar; Padhyegurjar, Shekhar Bhikaji (Indian Journal of Community Health, 2012)
Background: Education sector plays an important role in imparting vital information regarding HIV AIDS to large number of adolescents. The present study was carried out to assess the baseline level of knowledge and attitude regarding HIV / AIDS and retention of various aspects of information over the period of one year among ninth standard school students in Mumbai. Methods and Material: The present study was designed as a school based interventional follow up study. Health education sessions on HIV/AIDS were conducted. Pre test, immediate post test, along with a follow up post test at six months and one year were administered. SPSS (Version 16) and Excel software were used for statistical analysis. Z tests for difference between proportions were applied. Results: The proportion of correct responses regarding some of the aspects of knowledge of HIV / AIDS significantly increased on health education intervention. However, no significant change in the proportion of correct responses regarding blood donation leading to HIV transmission was observed. Significant waning (p < 0.01) away of the effect of health education has been observed in some important aspects especially regarding spread without being aware of transmission, involvement of infected needles, condoms as mode of prevention and no complete cure till date. Though there is a general acceptance of HIV positive patients, attitudes involving sexual mode of transmission, drug abuse and homosexuality did not show positive change post intervention. Conclusions: Health education sessions were very effective in increasing knowledge. However, students tend to lose information regarding certain aspects. We thus need strategies for reinforcing knowledge as well as attitude aspect in school AIDS education.